Walking the Walk: The Presence of Core Educational Leadership Standards in the Development and Implementation of Partnership Academies - Alex RedCorn (Educational Considerations, 2016)
A guest editor commentary. As repeatedly mentioned throughout this themed issue of Educational Considerations, the Kansas State University partnership academy model was built on the foundational principle of improving educational leadership training by creating a learning environment that better merges theory and practice.
Keywords: Core Educational; Standards; leaders; Student; commentary; Stakeholder; network; classroom; ecosystem